Ecology and biology of sea cucumbers in mangrove ecosystems of Babatngon, Leyte, Philippines - Romero, Maevel M.; Cabansag, Jerome Benedict P. (2013)
Sea cucumbers are echinoderms, under class Holothuroidea, that support a global market in fisheries. At present this market is severely exploited, which eventually caused depletion of the resource. This study was conducted from August 2012 to January 2013 and aimed to assess sea cucumbers in mangrove areas on the shallow waters of Babatngon, Leyte, Philippines. Species ecology and biology were analyzed for their diversity, length-weight relationship, gonadal development and gut content. Specimens were collected from the barangays Sangputan, District I, and Uban, which were alternatively visisted twice. During sampling, three 100 meter square (50 m x 2 cm) belt transects were laid parallel to the shore. A total of 104 individuals were collected in a total area of 1800 meter square and five species were identified consisting of Holothuria leucospilota, H. atra, H. impatiens, H. erinaceus. The population density of sea cucumbers in Babatngon is 0.058/meter square. District I exhibited the greatest species richness diversity index value of 0.652 and showed the greatest evenness index value of 0.940. For gonadal development, only 54.7% of the dissected specimens had gonads of which Gonado-somatic Index (GSI) ranged from 0.554-33.378. The reproductive stage with the greatest frequency is the male in maturing stage that constituted 21% of all dissected specimens. Examination of the gut revealed contents very similar with the substrate make up, which was composed of silt, sand with shell and sea weed fragments.